Effects of Solvent System and Storage Condition on Chemical Stability of 5(alpha)-Reductase Inhibitor Compounds in Tectona grandis L.f. Leaf Extracts - Insumrong, Kamonlak; Waranuch, Neti; Ingkaninan, Kornkanok; Tanuphol, Nutchaninad; Wisuitiprot, Wudtichai; Wongwad, Eakkaluk; Ngamdokmai, Ngamrayu; Suphrom, Nungruthai (Trends in Sciences, 2024)
Tectona grandis has been reported for its composition of two 5α-reductase inhibitors, specifically (+)-eperua-8,13-dien-15-oic acid (1) and (+)-eperua-7,13-dien-15-oic acid (2). These compounds exhibit potential as markers, enabling the standardization of leaf extracts during pre-formulation and formulation development. This study examined the effects of solvent system, pH, temperature and light on the stability of compounds 1 and 2 in the ethanolic extract and the ethanolic extract in PG with PEG-40 as a solubilizer. The remaining amount of the compounds at all test conditions was analyzed using HPLC. Compounds 1 and 2 exhibited greater stability in acidic solutions compared to neutral or basic environments. Their degradations were susceptible to light, particularly compound 1 of the ethanolic extract in PG. Both compounds in the solution form of the extract degraded rapidly at high temperature, whereas the present of PG minimized their degradation when the light was protected. According to the Q10 method, the calculated shelf-life of the extracts was 1.48 years. The extracts should be stored or prepared as a non-aqueous form or otherwise in a slightly acidic solution with appropriate light protection measures. The pre-formulation information obtained from this study holds significant value in informing the design and development of forthcoming anti-hair loss medications. HIGHLIGHTS Stability assessment of 5α-reductase inhibitors in teak extracts with solubilizers Shelf life of 2 inhibitors in prepared extracts was predicted using Q10 method This data is useful for the design and development of future anti-hair loss drugs GRAPHICAL ABSTRACT